Automatic meter reading and flexible billing schemes for energy transaction. - Perpustakaan UGM, i-lib ([Yogyakarta] : Program Magister Manajemen UGM, 2001)
Anticipating the free market and free competition era, an electric utility will face increasing request from its customers. The demands will be vary according to their various requirements. These requirements will stimulate the utility to innovate the best strategy for improving its services. One important aspect to satisfy its clients is by providing an automatic meter reading and a flexible billing payments. This paper describes the implementation of an automatic meter reading and some flexible billing payment schemes using medium voltage distribution line.